Factors influencing N95 respirator use among healthcare workers in a TB specialized hospital, Bangladesh - Sayeeda Tarannum; Abu-Hena Mostofa Kamal; Mohammad Tauhidul Islam; Md. Ariful Islam; Kamal Ibne Amin Chowdhury; Shirina Akhter; Afsana Sharmin; Emily S. Gurley; Sayera Banu; Md. Saiful Islam (PLoS ONE, 2026)
Background Healthcare workers (HCWs) in public tertiary care hospitals, including chest diseases hospitals, experience a substantial tuberculosis (TB) burden, with 40−48% demonstrating baseline TB infection and incidence rates of 4.2–4.8 per 100 person-years, indicating occupational exposure in high TB-burden settings. TB infection prevention and control (IPC) guidelines recommend that HCWs wear N95 respirators in pulmonary TB patient areas. To ensure appropriate use of N95 respirators by HCWs, an understanding of the barriers and facilitators associated with respiratory protection is needed. This study explored factors influencing N95 respirator use and reuse among HCWs in a TB-specialized tertiary care hospital in Bangladesh. Methods Between December 1, 2013, and June 05, 2014, a field team consisting of five social scientists conducted a qualitative study to explore the factors influencing N95 respirator use and reuse among HCWs in a TB-specialized, tertiary care hospital in Bangladesh. We initially conducted a day long training workshop with 28 HCWs (doctors, nurses and ancillary workers) working in two multi-drug resistant (MDR) TB inpatient wards on the proper use, reuse, and storage of respirators. Participants also underwent N95 respirator fit testing and received a two-month supply (60 days) of N95 respirators. We also conducted observations with 22 HCWs before and after the workshop to document use of N95 respirators and in-depth interviews with the 24 HCWs to explore TB risk perceptions, and the reported barriers and facilitators of N95 respirator uses. Results At baseline, N95 respirators use was high among nurses (8/9), whereas none of the doctors and ancillary workers used N95 respirators. Post-workshop observation findings showed that the use of N95 respirators remained highest among nurses (11/12) compared to doctors (1/5) and ancillary workers (2/5). Perception that N95 prevents germs from entering the body, the feeling of increased confidence when wearing them and concerns about MDR-TB were identified as key motivators for respirator use. In contrast, misperceptions that long-term exposure to TB confer immunity against infection, discomfort, lack of motivation from senior colleagues, pain, difficulties in accessing respirators, communication challenges, fogging of spectacles and cumbersome storage for reuse were identified as the main barriers to consistent N95 respirator use by HCWs. Conclusion N95 respirator use among HCWs was feasible but varied substantially across professional groups, with consistently higher uptake among nurses. Persistent behavioral, structural, and institutional barriers limited consistent use. Addressing misconceptions, improving access and storage systems, strengthening leadership support, and reinforcing institutional policies may enhance adherence to respirator use in high TB-burden settings.